1998
DOI: 10.1073/pnas.95.3.1091
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of cyclin D-dependent kinase and titration of p27 Kip1 regulated by mitogen-activated protein kinase kinase (MEK1)

Abstract: A constitutively active form of mitogenactivated protein kinase kinase (MEK1) was synthesized under control of a zinc-inducible promoter in NIH 3T3 fibroblasts. Zinc treatment of serum-starved cells activated extracellular signal-regulated protein kinases (ERKs) and induced expression of cyclin D1. Newly synthesized cyclin D1 assembled with cyclin-dependent kinase-4 (CDK4) to form holoenzyme complexes that phosphorylated the retinoblastoma protein inefficiently. Activation of the MEK1͞ERK pathway neither trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
360
9
4

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(387 citation statements)
references
References 78 publications
14
360
9
4
Order By: Relevance
“…Erk kinase facilitates S-phase DNA damage checkpoint D Wu et al at 50 mM slightly reduced G1-phase progression, an observation consistent with a role of Erk kinase in the facilitation of G1 Cdk activation (Lavoie et al, 1996;Weber et al, 1997;Cheng et al, 1998), U0126 attenuated HU-induced S-phase arrest in MCF7, MEF, NIH3T3, and HCT116 cells (Table 1). Another MEK inhibitor, PD98059, essentially produced the same results (data not shown), suggesting a general role for Erk in DNA damage-induced S-phase checkpoint activation.…”
Section: Hu Activates Erk Kinase Via Mek1supporting
confidence: 65%
See 1 more Smart Citation
“…Erk kinase facilitates S-phase DNA damage checkpoint D Wu et al at 50 mM slightly reduced G1-phase progression, an observation consistent with a role of Erk kinase in the facilitation of G1 Cdk activation (Lavoie et al, 1996;Weber et al, 1997;Cheng et al, 1998), U0126 attenuated HU-induced S-phase arrest in MCF7, MEF, NIH3T3, and HCT116 cells (Table 1). Another MEK inhibitor, PD98059, essentially produced the same results (data not shown), suggesting a general role for Erk in DNA damage-induced S-phase checkpoint activation.…”
Section: Hu Activates Erk Kinase Via Mek1supporting
confidence: 65%
“…This result further supports a facilitating function of Erk kinase in S-phase checkpoint activation. As Erk activity facilitates G1-phase progression (Cheng et al, 1998), inhibition of Erk activation by U0126 may lead to G1-phase arrest, and thus reduces the magnitude of HU-induced S-phase arrest as a consequence of the inability of cells to enter S phase. However, this possibility is very unlikely, since (1) Ctrl: mock (DMSO) treated; U: U0126 (50 mM); HU: hydroxyurea (1 mM for MCF7 and HCT116, 0.3 mM for MEF and NIH3T3).…”
Section: Hu Activates Erk Kinase Via Mek1mentioning
confidence: 99%
“…p27 KIPl is generally expressed at high levels in cells arrested by treatment with transforming growth factor-b, contact inhibition or serum deprivation (Koff et al, 1993;Polyak et al, 1994). In contrast, p27 KIP1 declines in the presence of mitogenic growth factor signalling or interleukin-2 (Nourse et al, 1994;Cheng et al, 1998). p27 KIP1 -deficient mice develop a variety of abnormalities including multiorgan hyperplasia and pituitary tumours (Nakayama et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…p27 Kip1 protein is mainly degraded by the ubiquitin-proteasome pathway. Recently, several investigators indicated that cyclins D and E can regulate p27 Kip1 protein levels in some cells (2,3,36). Furthermore, multiple CDK inhibitors are necessary to maintain cell cycle progression in this system (37).…”
Section: Discussionmentioning
confidence: 99%